Diversity-oriented synthesis of stereodefined tetrasubstituted alkenes via a modular alkyne gem-addition strategy - Di, Xuan; Zhou, Sitian; Qin, Yali; Li, Wenjun; Zhang, Yue; Zhang, Jie; Shen, Xu; Han, Jie; Xie, Jin; Jin, Hongming (Nature communications, 2025)
Stereocontrolled construction of tetrasubstituted olefins has been an attractive issue yet remains challenging for synthetic chemists. In this manuscript, alkynyl selenides, when treated with ArBCl 2 , are subject to an exclusive 1,1-carboboration, affording tetrasubstituted alkenes with excellent levels of E -selectivity. Detailed mechanistic studies, supported by DFT calculations, elucidates the role of selenium in this 1,1-addition process. Coupled with subsequent C-B and C-Se bond transformations, this 1,1-addition protocol constitutes a modular access to stereodefined all-carbon tetrasubstituted alkenes. The merit of this approach is demonstrated by programmed assembly of diverse functionalized multi-arylated alkenes, especially enabling the stereospecific synthesis of all six possible stereoisomers of tetraarylethene (TAE) derived from the random permutation of four distinct aryl substituents around the double bond. The diversity-oriented synthesis is further utilized to explore different TAE luminogenic properties and potential Se-containing antitumor lead compounds. Tetrasubstituted alkenes are found in bioactive compounds and materials, but modular stereospecific synthesis of these compounds remains challenging due to reactivity and selectivity issues of the intermediate compounds. Here, the authors disclose a carboboration of alkynyl selenides, which provides an intermediate with two readily distinguishable sites of functionalization, providing rapid access to stereodefined tetrasubstituted alkenes.